A Mechanism for the Development of Chronic Traumatic Encephalopathy From Persistent Traumatic Brain Injury. (May 2019) - Demock, Melissa; Kornguth, Steven
A mechanism that describes the progression of traumatic brain injury (TBI) to end-stage chronic traumatic encephalopathy (CTE) is offered in this article. This mechanism is based upon the observed increase in the concentration of both tau protein and of human leukocyte antigen (HLA) class I proteins; the HLA increase is expressed on the cell membrane of neural cells. These events follow the inflammatory responses caused by the repetitive TBI. Associated inflammatory changes include macrophage entry into the brain parenchyma from increased permeability of the blood-brain barrier (BBB) and microglial activation at the base of the sulci. The release of interferon gamma from the microglia and macrophages induces the marked increased expression of HLA class I proteins by the neural cells and subsequent redistribution of the tau proteins to the glial and neuronal surface. In those individuals with highly expressed HLA class I C, the high level of HLA binds tau protein electrostatically. The ionic region of HLA class I C (amino acid positions 50-90) binds to the oppositely charged ionic region of tau (amino acid positions 93-133). These interactions thereby shift the cellular localization of the tau and orient the tau spatially so that the cross-linking sites of tau (275-280 and 306-311) are aligned. This alignment facilitates the cross-linking of tau to form the intracellular and extracellular microfibrils of tau, the primary physiological characteristic of tauopathy. Following endocytosis of the membrane HLA/tau complex, these microfibrils accumulate and produce a tau-storage-like disease. Therefore, tauopathy is the secondary collateral process of brain injury, resulting from the substantial increase in tau and HLA expression on neural cells. This proposed mechanism suggests several potential targets for mitigating the clinical progression of TBI to CTE.